Efektivitas Pelaksanaan Program Sembako di Desa Karya Indah Kecamatan Tapung Kabupaten Kampar - Abdiana, Ella; Zulhaida, Zulhaida; Nurjana, Mike (IRPI Publisher, 2022)
This study aims to determine the effectiveness of the implementation and the inhibiting factors of the Sembako Program in Karya Indah Village, Tapung District, Kampar Regency. With research indicators on target accuracy, program socialization, program objectives, and program monitoring. The type of research used is qualitative research with qualitative descriptive data analysis techniques with percentages. From this study it can be concluded that in Karya Indah Village, Tapung District, Kampar Regency, it is not yet effective enough in implementing the Basic Food Program seen from the inaccuracy of targeting the community receiving the Basic Food Program, the KPM still lacks understanding of the social assistance they receive, as well as monitoring that has not been carried out to KPM. so that the achievement of goals has not been carried out optimally.